Analisis Implementasi Penguatan Pendidikan Karakter Melalui Budaya Sekolah di SD Unggulan Al - ‘Izzah Bandung - Neng Serli; Tin Rustini; Yayang Furi Furnamasari (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The purpose of this study is to analyze how the implementation of strengthening character education through school culture, school constraints and solutions are carried out to overcome obstacles in the implementation of strengthening character education through school culture. The method used in this study is a descriptive analysis method, with a qualitative approach. The results of the study showed that the implementation of Strengthening Character Education through School Culture was carried out through the school's vision and mission, habituation, appeal, discipline, subject integration, extracurricular, uniqueness and characteristics of the school, cooperation between parents and committees. In addition, several obstacles were also found, namely those found in School Stakeholders, Parents, facilities and infrastructure. Solutions were also found to overcome obstacles in the implementation of strengthening character education, namely conducting weekly evaluations, synergy with parents and school development plans.